Impact of amount and time of nitrogen fertilizer usage on cultivating Spruce (Picea abies L.) seedlings - Alireza Zare; Vladimir A. Brinsev (تحقیقات جنگل و صنوبر ایران, 2009)
In order to amend usage effects of N fertilizer on Spruce seedlings and reduce its environmental compacts, an experiment was conducted during years 2005-2006 to investigate effects of N fertilizer application amount and time on growth of one and two year old seedlings of Spruce (Piceaabies) in a nursery near Moscow city. The fertilizer application time was considered on account of phenological stages. The fertilizer amount and time treatments were applied simultaneously. The fertilizer amount treatments consisted of 0 (control), 40, 110 and 180 kg/ha. The fertilizer time treatments for two year seedlings consisted of tree and six phenological stages during 2005-2006 and for one year old seedlings consisted of four phenological stages in 2005. This trial was carried out under spilt plot in completely randomized block design with three replications in the nursery. Results showed that application of N fertilizer time treatments affected the seedlings height and diameter greater than the amount treatments. Interaction of fertilizing time and fertilizing amount treatment at first growth period on seedlings heights was significant (probability of 95%) at two fertilizing time treatments, including: 5.07.05 or interval between completing root system and stop of summer growth (difference between control and the other fertilizer amount treatments) and 23.08.05 or interval of forming lateral bud and beginning formation of apical bud (difference between both fertilizing levels of 110 and 40 kg/ha and in one side control and 180 kg/ha on the other side). From time point of view, most nutritive requirements of the two year old seedlings, were observed at phenological stages of intensive shoot growth and increment and bud development (G1-B2), indicating that minimum consumption of fertilizer in this period was able to leave equal or greater effect on seedling growth compared to maximum consumption at the other phenological stages.